Hubungan Keadaan Kimiawi dan Mikrobiologik Ikan Pindang Naya Pada Penyimpanan Suhu Kamar Dengan Sifat Organoleptiknya = Chemical, Microbiological, and Organoleptic Characteristics Relationship of Salt-Boiled Fish - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Research on salt-boiled fish of kembung (Rastreliger negleclus) has been conducted. Ungutted and undressed fish was boiled in 20% w/v salt solution for 20 minutes. This treatment produced sail-boiled fish containing 3% salt and 60% moisture. During five days storage at room temperature (c.a. 27Â°C), there were no change in moisture content, while the concentration of nitrogen volatile, malonaldehyde, peroxide, for-moll value, and acidity were increased gradually. Either salt content or water activity of salt-boiled fish did not significantly increased as the storage time increase. Growth of bacteria, fungi, and yeast were increase during storage. It Was obtained a relationship between chemical and microbiological characteristics of salt-boiled Fish with its organoleptic properties. Slightly higher score than normal acceptable was given by the panelists onto two days storage of salt-boiled fish, but it did not on the category of preferable. The salt-boiled fish which was stored for two days has nitrogen volatile content 207,10 ppm, while peroxide and acidity (as acetic acid) were 8,75 Mot/kg and 4,66 mg/100 g respectively. Total bacteria was found 67 x le cfu/g. At three days storage salt-boiled fish was moulded and did not prefer by the panelists.